Enhancement of Kinetic Hydrate Inhibitor Polyvinylpyrrolidone(PVP) with Addition of Polyethyleneoxide (PEO) - Afiq Safeeuddin bin Nordin, Afiq Safeeuddin (Universiti Teknologi Petronas, 2012)
Gas hydrates are well known problem in oil and gas industry that cost millions of dollars in production and transmission pipelines. By definition, hydrate is a solid clathrate structure, non-stoichiometric, formed due to the nucleation of polyhedral water cages which encapsulates the “guest” molecules comprises of lighter hydrocarbon such as methane and ethane at elevated pressure and low temperature. The concern on hydrate is due to its problem in blocking the pipeline, by disrupting the flow assurance capabilities in production. Hydrate is very common in a dedicated gas well which are rich in inert gases that might contribute as major constituents of hydrate structure such as carbon dioxide, sulphur dioxide and nitrogen. Basically, hydrate can be divided into 3 main clusters which are : 1. Structure 1: Very common type encases of carbon dioxide, and low hydrocarbon molecules such as methane and ethane. 2. Structure 2 :Hydrate encases of nitrogen, propane and butane 3. Structure H : hydrate encases of large mole structure such as neohexane, cyclopentane. 3 alternatives used in oil and gas industry to inhibit the hydrate formation and growth. 1. Thermodynamic Inhibitor(THI) : Earliest and most common method for controlling hydrate. THI lowers the freezing point of the aqueous solution, similar to anti-freeze agent. Example of THI is methanol or glycol. 2. Anti-Agglomerants(AA) : It allows the amount of gas hydrate but act to suppress the propagation and agglomeration by dispersing the hydrate in oil or condensate phase. 3. Kinetic Hydrate Inhibitor : Motivation of KHI development believes that this type of inhibitor delay the initial hydrate nucleation. Extensive research believes that the KHI can also lengthen the time required for succession growth of hydrate after the first nucleation. In this project, Polyethyleneoxide (PEO) is non-ionic, water soluble, linear polymer is used as an additives added to Polyvinylpyrrolidone(PVP). PEO is actually made up into a long chain of polymer with n repeating units. PEO in water exhibits and inverse solubility temperature relationship. The objective of the work undertaken in this study is to check on the performance of PEO in adhering to existing kinetic hydrate inhibitor in lengthening the induction time. The 9 PEO will be added to the PVP in trace amount to see the performance of the new formulation to further lengthen the induction time for hydrate formation and growth. In particular, the existing PVP has limited efficiency in lengthening the hydrate induction time. Since PEO exists abundantly in nature, it is feasible to use this kind of additives as catalyst in kinetic hydrate inhibitor. In this study, Micro Differential Scanning Calorimetry (DSC) will be used to experiment the heat flow that really occurs in hydrate labile cluster until its bulk phase formation. Heat flow in this structure can be either endothermic or exothermic reaction. From the trend of the graph produced, one can easily identify the induction time for hydrate formation with respective of composition of kinetic hydrate inhibitor. Besides, the result of hydrate induction time will be compared with other potential kinetic hydrate inhibitor which is the Calcium Magnesium Acetate (CMA). Although the study of kinetic hydrate inhibitor is still new, but the expected result is believed to be promising in terms of its economic viability and environmental friendliness. KHI will beat the Thermodynamic Hydrate Inhibitor (THI) as low dosage and cost effective hydrate inhibitor